Family Caryophyllaceae in the flora of Central Kazakhstan: species composition, spreading, practical use - Mussina, R.T.; Silantjeva, M.M.; Ishmuratova, M.Yu.; Gavrilkova, E.A.; Tleukenova, S.U.; Nurkenova, A.T. (Karagandy University of the name of academician E.A. Buketov, 2024)
This article analyzes the species composition of the family Caryophyllaceae of the flora of Central Kazakhstan within the Karaganda and Ulytau regions, the distribution of identified taxa, ecobiomorphological features and phytoprotective status. It was revealed that the family Caryophyllaceae includes 80 species from 18 genera, which is 44.4% of the species flora of this family of Kazakhstan and 7.2% of the total number of species of the flora of Central Kazakhstan. The leading genera by number of species are Silene L. (28 species) and Dianthus L. (11 species). Endemic species are 2 taxa. Phytoprotective status has 1 species, which is included in rare and endangered plants of Karaganda region. In relation to moisture conditions, mesophytes (12 species) prevail among the described taxa, xeromesophytes (19 species) are in the second place, and mesoxerophytes (16 species) are in the third position. Analysis of life forms showed predominance of herbaceous perennial (60 species) and annual (16 species) forms. Among the species of the family Caryophyllaceae, the following economically valuable groups were noted: weedy, medicinal, poisonous, and suitable for perfumery and cosmetic purposes, ornamental, technical, fodder and honey-bearing groups.
Орталық Қазақстанның Caryophyllaceae тұқымдасының өкілдері: түрлік құрамы, таралуы және пайдалану мүмкіндіктері
Представители семейства Caryophyllaceae Центрального Казахстана: видовой состав, распространение и возможности использования
Keywords: family Caryophyllaceae; flora; Central Kazakhstan; species composition; ecological groups; life forms; useful properties; phytoprotective status